The role of Desmodium intortum, Brachiaria sp. and Phaseolus vulgaris in the management of fall armyworm Spodoptera frugiperda (J. E. Smith) in maize cropping systems in Africa - Scheidegger, Laetitia (Pest Manag Sci, 2021)
BACKGROUND: The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith) is a serious pest of maize. Farming systems such as push‐pull or maize‐legume intercropping have been reported to reduce FAW infestations significantly. However, the exact mechanisms involved in FAW management have not been practically elucidated. We therefore assessed larval host preference, feeding and survival rate when exposed to four host plants commonly used in push‐pull and legume intercropping. We also compared adult moths' oviposition preference between maize and other grasses used as trap crops in push‐pull. RESULTS: The larval orientation and settlement study showed that maize was the most preferred host plant followed by bean, desmodium and Brachiaria brizantha cv Mulato II. The larval arrest and dispersal experiment showed that mean number of larvae was significantly higher on maize than on Desmodium or B. brizantha cv Mulato II. However, no significant differences were found between maize and bean after 24 h. Maize was the most consumed plant, followed by bean, desmodium and finally brachiaria. The mean percentage of survival to the pupation stage was significantly higher on maize. The study on FAW oviposition preference showed no significant differences in egg deposited between maize and other grasses. However, B. brizantha cv Xaraes, which received more eggs than maize, could be a promising alternative to B. brizantha cv Mulato II for the control of FAW. CONCLUSION: The study provides a better understanding of the mechanisms involved in the control of fall armyworm under the push‐pull and maize legume intercropping. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.